FK506 Attenuated Pilocarpine-Induced Epilepsy by Reducing Inflammation in Rats - Wang, Aihua; Si, Zhihua; Li, Xiaolin; Lu, Lu; Pan, Yongli; Liu, Jinzhi (Frontiers in Neurology, 2019)
Background: The status epilepticus (SE) is accompanied by a local inflammatory response and many oxygen free radicals. FK506 is an effective immunosuppressive agent with neuroprotective and neurotrophic effects, however, whether it can inhibit the inflammatory response and attenuate epilepsy remains unclear. Objective: This study aims to clarify the effect of FK506 on inflammatory response in rats with epilepsy. Methods: A total of 180 rats were randomly and equally divided into the control group, epilepsy group, and FK506 group. The rat SE model in the epilepsy group and FK506 group was induced by lithium chloride combined with pilocarpine. In the FK506 group, FK506 was given before the injection of pilocarpine. The control group was given the same volume of saline. Then the effect of FK506 on epilepsy in rats and the changes of inflammatory factors and free radicals in hippocampus were examined using hematoxylin and eosin (HE) staining, immunohistochemistry, quantitative real-time polymerase chain reaction (qRT-PCR), and western blotting. Results: FK506 ameliorated the course of pilocarpine-induced epilepsy and the neuronal loss in the rat hippocampus after SE. FK506 reduced the increased content of nitric oxide (NO), superoxide dismutase (SOD), and malondialdehyde (MDA) in the hippocampus after SE. Besides, FK506 also significantly reduced the levels of factors involved in inflammatory response such as vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), tumor necrosis factor-α (TNF-α), and Protein Kinase C δ (PKCδ) that rise after epilepsy. Conclusion: FK506 ameliorated the course of pilocarpine-induced epilepsy, significantly reduced free radical content, and inhibited the expression of inflammatory factors, which provided a theoretical basis for the application of FK506 in the treatment of epilepsy.